A systematic business process management application of an imports process on a commercial company (2020)
In recent years, companies have tried to understand their processes' functionality and response capability to the forces of the environment using information systems. This research developed an automated Business Process Management (BPM) model of the import process in a commercial company located in Colombia. First, a survey was applied to the stakeholders to ascertain the challenges presented at the company' import process. Later, a process flow was proposed based on BPM. The model results indicate a 43% reduction in the execution times of activities in the import area, a 30% decrease in default costs, and a 70% reduction in storage costs for the company.